1988
DOI: 10.1051/jphyscol:19888906
|View full text |Cite
|
Sign up to set email alerts
|

Initial Slope of the Hysteresis Curve

Abstract: An analytical expression for the initial slope T of the hysteresis curve is derived for a stripe domain structure in a thin magnetic film, giving that T-' is proportional to t-'I2 (t = film thickness). This is confirmed by measurements on RF sputtered CoCr films with 20 nm 5 t 5 950 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1994
1994

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In perpendicular media, the demagnetizing field shears the hysteresis loop. It has been shown that this shearing depends upon the demagnetizing factor, the thickness and the magnetic properties of the film [4]. These demagnetizing effects will be combined with the moving parameter when fully describing the model.…”
Section: Introductionmentioning
confidence: 99%
“…In perpendicular media, the demagnetizing field shears the hysteresis loop. It has been shown that this shearing depends upon the demagnetizing factor, the thickness and the magnetic properties of the film [4]. These demagnetizing effects will be combined with the moving parameter when fully describing the model.…”
Section: Introductionmentioning
confidence: 99%